Prosthetic scenographies: scenographic extension of the senses and mediation of the performance space in Tower. Issue 1 (2nd January 2018) - Thornett, Lucy
ABSTRACT: In this article I provide an account of how the spectator's senses can be extended and mediated by scenography to argue for an expanded understanding of scenography's affective operation in performance. This is discussed in the context of practice-research project Tower, a site-led performance presented in London in 2017 that is performed in a high-rise building and watched from the street through binoculars, with the audience listening to a binaural recording of the performers' movements through headphones. The binaural soundscape and the binoculars are conceived of as mediating prostheses that extend the bodies of the audience to create a mediated sensory proximity that is experienced in disjunction with the physical distance of the performance. Drawing on perspectives on sensory and spatial perception from phenomenology and cognitive science, I analyse my own experience of the work from my dual perspective as creator and spectator. I argue that the sensory disjunction in Tower produces an affective unreality, which heightens the fictional space of the performance within the real site. I argue that by considering the mediating prostheses as part of the scenography, we open up new ways to think about both mediating technologies and how scenography operates on audiences.